Respiratory and gastrointestinal complications of caustic ingestion in children. Issue 5 (20th April 2005) - Turner, A; Robinson, P
Abstract : Objectives: To determine circumstances surrounding the ingestion of caustic substances, the incidence of respiratory and gastrointestinal symptoms at presentation, and the degree of investigation and active treatment during hospitalisation. Long term respiratory and gastrointestinal sequelae were also studied. Design: Retrospective case note study covering a 10 year period. Setting: Tertiary children's hospital. Patients: Children and adolescents presenting following caustic ingestions to the Royal Children's Hospital, Melbourne. Main outcome measures: Requirement for interventional oesophagoscopy/bronchoscopy, respiratory support or admission to intensive care, and long term gastrointestinal or respiratory sequelae noted. Results: Thirty two cases of caustic ingestion were identified in 31 patients (median age 2.6 years; 78% boys). The average time in hospital was 2 days. Two patients (6%) required intensive care nursing, and both required intubation with mechanical ventilation (average 33 hours). Thirty patients (97%) underwent diagnostic oesophagoscopy, and two underwent laryngoscopy or bronchoscopy for visualisation of the upper airway. No patient had long term respiratory consequences. Two patients (6%) sustained significant oesophageal injuries requiring interventional oesophagoscopy. Conclusions: Caustic ingestion is overrepresented in boys. Most ingestions involve household cleaning products. Symptoms on admission do not usually require intensive care admission. Gastrointestinal symptoms predominate at presentation, however, these are usually mild. Respiratory symptoms are uncommon and respiratory involvement requiring intervention is rare, although the presence of respiratory symptoms should be viewed as potentially serious. Long term sequelae of caustic ingestion are rare and in this series only affected the gastrointestinal tract. The indications for diagnostic endoscopy need further evaluation.